The role of legumes in mixed pastures - Whitney, A.S. (International Center for Tropical Agriculture, 1982)
Legumes can contribute greatly to pasture production by providing high protein forage, especially during the dry season when grass quality is poor. Little nitrogen (N) is transferred underground by actively growing legumes, but aboveground transfer of N, principally in legume leaf litter, green leaf which is trampled into the soil by grazing animals, urine from animals grazing legumes, and feces, is significant. Management alternatives to maximize the legume N contribution are discussed.